2015
DOI: 10.1259/dmfr.20140224
|View full text |Cite
|
Sign up to set email alerts
|

Technical aspects of dental CBCT: state of the art

Abstract: As CBCT is widely used in dental and maxillofacial imaging, it is important for users as well as referring practitioners to understand the basic concepts of this imaging modality. This review covers the technical aspects of each part of the CBCT imaging chain. First, an overview is given of the hardware of a CBCT device. The principles of cone beam image acquisition and image reconstruction are described. Optimization of imaging protocols in CBCT is briefly discussed. Finally, basic and advanced visualization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
245
1
30

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 350 publications
(330 citation statements)
references
References 38 publications
3
245
1
30
Order By: Relevance
“…This is in line with the decreased spatial resolution at larger voxel sizes, 29,30 leading to a loss of detail in the trabecular bone, which can be seen as a "merging" of neighbouring trabeculae. For anisotropy and plateness, no (or little) effect of voxel size was seen.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This is in line with the decreased spatial resolution at larger voxel sizes, 29,30 leading to a loss of detail in the trabecular bone, which can be seen as a "merging" of neighbouring trabeculae. For anisotropy and plateness, no (or little) effect of voxel size was seen.…”
Section: Discussionsupporting
confidence: 57%
“…When comparing the volume of the voxels instead, it can be calculated that a 0.080-mm voxel fits 3.8 times in a 0.125-mm voxel, 15.6 times in a 200-mm voxel and 52.7 times in a 300-mm voxel. While noise steadily increases at smaller voxel sizes if mAs is not increased accordingly, 30 it appears that the noise has a smaller effect on bone structure analysis than voxel size. Ibrahim et al showed no significant effect of CBCT exposure time, but a significant effect of voxel size (which was varied by changing the FOV size), on Tb.…”
Section: Discussionmentioning
confidence: 96%
“…These reports are consistent with our results. Pauwels et al 29 stated that image noise can be reduced by averaging multiple consecutive slices. Our results also showed that with thicker slices, the image noise was reduced (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] The remainder of this section will focus on experimental findings related to the accuracy and clinical application of GV in CBCT. Studies on non-dental CBCTs will not be discussed, although the inherent issues and findings are similar, 29,30 and corrections have been proposed that may be applicable for dental CBCT as well.…”
Section: Applicability Of Hounsfield Units In Cbctmentioning
confidence: 99%